Manure Management in the Kenya Highlands: Practices and Potential - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
JK Lekasi, JC Tanner, SK Kimani, and PJC Harris. HDRA Publications. 1998. 32 pp.ISBN 0 905343 25 5.Free of charge.Henry Doubleday Research Association,Ryton-on-Dunsmore, Coventry CV8 3LG, UK.Fax: +44 1203 639 229Email: enquiry@hdra.org.uk